KEUNGGULAN BERSAING : MANAJEMEN STRATEGI SUMBER DAYA MANUSIA - Dina Sarah Syahreza; Alfyyah Zahira Hakim; Nadhira Zahra Siregar; Devi Yulia; Ahmad Hafiz Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2023)
One of the important aspects of an organization or company is its human resources. Human Resources (HR) are every individual who uses their abilities to work or contribute to an organization or company. A good relationship between workforce (HR) and the company can make the company better, so human resource management (HRM) is needed to be the link between them. This research aims to examine in more depth the role, function and competitive advantage of strategic human resource management (HRM). The type of research carried out is descriptive research using library research data collection techniques. The research results showed that the role of HRM generally includes the role of HRM, including recruiting and placing employees according to job descriptions, developing employee performance, promoting and offering HR requests, monitoring the implementation of labor legislation within the company, and arranging transfers, retirement, dismissal and severance pay. The function of HRM consists of: (1) managerial function, including planning, organizing, directing and controlling (2) operational function, including procurement, development, compensation, integration, maintenance, discipline and termination Competitive advantage of human resource strategic management (HRM ) can be done by being selective in recruitment, providing salaries or wages that are in accordance with employee competence and potential, paying incentives such as guarantees, recognition and fairness as well as providing training and development that is beneficial to the workforce.